Biphasic synovial sarcoma of the epiglottis: Case report and literature review. Issue 3 (June 2018) - Wigand, Marlene C.; Hoffmann, Thomas K.; Barth, Thomas F.E.; Veit, Johannes
Abstract: Synovial sarcomas are rare malignant tumors supposed to arise from pluripotent mesenchymal stem cells predominantly affecting the deep soft tissue of the lower and upper extremities in young adults. The occurrence of this tumor entity in the head and neck is very uncommon and hence, timely diagnosis and treatment of synovial sarcoma in this region remain a challenge. We describe the clinical and molecular pathological features of a biphasic synovial sarcoma of the epiglottis, a site where the primary manifestation of this tumor entity has not been documented to date. With this background the existing literature is being reviewed. Whilst wide excision of synovial sarcoma is considered as the primary mainstay of therapy, (neo)adjuvant treatment strategies have been proposed to increase local control and prolong disease-free survival.